Pyoluteorin Produced by the Biocontrol Agent Pseudomonas protegens Is Involved in the Inhibition of Heterobasidion Species Present in Europe - Martina Pellicciaro; Elio Padoan; Guglielmo Lione; Luisella Celi; Paolo Gonthier (Pathogens, 2022)
Pseudomonas protegens (strain DSMZ 13134) is a biocontrol agent with promising antagonistic activity hinging on antibiosis against the fungal forest pathogens Heterobasidion spp. Here, by using High-Performance Liquid Chromatography coupled to Mass Spectrometry (HPLC-MS), we assessed whether monocultures of P. protegens (strain DSMZ 13134) produce the three major determinants of biocontrol activity known for the genus Pseudomonas: 2,4-diacetylphloroglucinol (2,4-DAPG), pyoluteorin (PLT), and pyrrolnitrin (PRN). At the tested culture conditions, we observed the production of PLT at concentrations ranging from 0.01 to 10.21 mg/L and 2,4-DAPG at a concentration not exceeding 0.5 mg/L. Variations of culture conditions involving culture medium, incubation temperature, and incubation period had no consistent influence on PLT production by the bacterium. Assays using culture medium amended with PLT at the same concentration of that present in cell-free filtrate of the bacterium, i.e., 3.77 mg/L, previously documented as effective against Heterobasidion spp., showed a remarkable activity of PLT against genotypes of all the four Heterobasidion species present in Europe, including the non-native invasive H. irregulare. However, such antifungal activity decreased over time, and this may be a constraint for using this molecule as a pesticide against Heterobasidion spp. When the bacterium was co-cultured in liquid medium with genotypes of the different Heterobasidion species, an increased production of PLT was observed at 4 °C, suggesting the bacterium may perform better as a PLT producer in field applications under similar environmental conditions, i.e., at low temperatures. Our results demonstrated the role of PLT in the inhibition of Heterobasidion spp., although all lines of evidence suggest that antibiosis does not rely on a single constitutively produced metabolite, but rather on a plethora of secondary metabolites. Findings presented in this study will help to optimize treatments based on Pseudomonas protegens (strain DSMZ 13134) against Heterobasidion spp.